O design dos livros de leitura da editora Francisco Alves (1900-1938): Felisberto de Carvalho e seus contemporâneos - Luiz Augusto do Nascimento (2017)
This research, on the design of reading books from the beginning of the 20th Century, aimed at analyzing the role played by the graphic-editorial project in the successful enterprise of Felisberto de Carvalhoss series of Reading books, published by Francisco Alves Publishers form 1900 to 1938. Assuming that the books design was a fundamental reason for their success, a documental investigation into Felisberto de Carvalhos books and some of his contemporary authors became relevant. We looked into the visual culture influence of the investigated period, as well as the impact of the limited technical resources (printing process and movable types) available at the time, in addition to the agents involved in the process of producing reading books at Francisco Alves Publishers. This research established a dialogue with editorial design studies, publishing history and didactic books, especially those dealing with the graphic aspects of literacy books and Reading development. In the analyzed books, the construction of the layout and their mancha gráficawere observed; the use of typography and of illustrations in accordance with the graphic project and the age group; the font size related to the legibility of the target public and the percentage of illustrations in the mancha gráfica. Thus, it was demonstrated that Felisberto de Carvalhos books, as opposed to his contemporarys works, presented a cohesive and coherent graphic-editorial project, were visually agreeable and attractive, which, among other factors, probably contributed immensely to the success of his publications. The pedagogical contribution of this research lies in the discussion and elucidation of the graphic and editorial aspects of didactic material, as well as the influence of the visual culture and printing techniques of the studied period in which those books were published.